2008
DOI: 10.1038/nri2304
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathogenesis of T-cell leukaemia and lymphoma

Abstract: T-cell acute lymphoblastic leukaemia (T-ALL) is induced by the transformation of T-cell progenitors and mainly occurs in children and adolescents. Although treatment outcome in patients with T-ALL has improved in recent years, patients with relapsed disease continue to have a poor prognosis. It is therefore important to understand the molecular pathways that control both the induction of transformation and the treatment of relapsed disease. In this Review, we focus on the molecular mechanisms responsible for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
334
3
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(349 citation statements)
references
References 94 publications
5
334
3
7
Order By: Relevance
“…Development and progression of T-ALL have been linked to mis-regulation of Notch signaling (Aifantis et al, 2008;Clappier et al, 2010). In particular, we previously showed that Notch3 intracellular domain (N3 IC ) transgenic (tg) mice develop a very aggressive T-ALL with high penetrance, representing a suitable model of the human disease (Bellavia et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Development and progression of T-ALL have been linked to mis-regulation of Notch signaling (Aifantis et al, 2008;Clappier et al, 2010). In particular, we previously showed that Notch3 intracellular domain (N3 IC ) transgenic (tg) mice develop a very aggressive T-ALL with high penetrance, representing a suitable model of the human disease (Bellavia et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, certain aspects about T-ALL make it a more aggressive disease with a poorer clinical outcome than B-ALL. T-ALL patients have a higher percentage of induction failure, and rate of relapse and invasion into the central nervous system (reviewed in Aifantis et al, 2008). The challenge to acquiring 100% remission in T-ALL treatment is the subset of patients (20-25%) whose disease is refractory to initial treatments or relapses after a short remission period due to drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…L'oncogenèse des LAL-T est multigé-nique, avec coexistence de plusieurs dérégulations oncogéniques chez le même patient [4]. Parmi les sousgroupes identifiés, figure l'important groupe TLX marqué par la surexpression des oncogènes TLX1 ou TLX3.…”
Section: Réarrangements V(d)j Du Tcr Et Différenciation Des Thymocytesunclassified
“…Ea CAT [4]. Un métabolisme primitif nécessite égale-ment que ces polymères soient capables de se replier dans des structures tertiaires stables ayant des fonctionnalités élaborées telles que la reconnaissance d'un ligand et la catalyse [5].…”
Section: Cbfa2unclassified